USO DO TEATRO PARA O ENSINO DA PARASITOLOGIA - Pereira de Oliveira, Rosivaldo; Ferreira Lima, Edmar; da Costa Brito, Clecina; Jossany Almeida Brito, Mayra; Cristhina Aragão Pereira, Cynara (Revista Form@re - Parfor/UFPI, 2026)
.